Zur Bedeutung der spezifischen Ausdauer im Fußball - eine Befundlage und Literaturübersicht - Oh, S.; Hartmann, U. (Leipziger Sportwissenschaftliche Beiträge, 2016)
In total 54 pre-post intervention studies on soccer-specific endurance were searched and analysed by using electronic data bank and literature lists. In most of the protocols training was performed twice weekly for six or eight weeks during the pre-season period or competition season by elite junior soccer players. As main training programs, four running protocols without ball or various forms with ball were found. The training effects were determined mostly using the result of a VO2max test or Yo-Yo intermittent recovery test. In all studies the effects of training programs were positively identified, in particularly, the high intensity training or small-sided soccer games were mostly recommended by authors to improve the soccer-specific endurance.